PENGARUH MODEL PEMBELAJARAN TERPADU TIPE CONNECTED BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR IPA - Nurjannah Nurjannah (Universtas Negeri Makassar, 2022)
The objective of this study is to determine the differences of study’s product in learning science between students who learned with connected model assisted picture media and students who learned with the direct instruction model. The population of this study is all of the fourth grade students in SDN 49 Pare-Pare in Gugus IV, District, in academic year 2019/2020, numbered 186 people. The sample of this study are two classes; they are the students in IVA numbered 28 people as the experiment group, and the students in IVB SDN 46 Pare-Pare numbered 28 people as the control group. The researcher decided the sample through random sampling. The research design of this study is quasi experiment with Non Equivalent Post-test Only Control Group Design. The data of study’s product gathered with the objective test. Then, the data was analyzed by using descriptive statistics and inferential statistics (t-test). The result shown that there are significant differences of study’s product in learning science between the groups of students who learned with connected model assisted picture media and students who learned with the direct instruction model. Those differences can be seen based on the result, the t-test is higher than ttable (ttest=3,815>ttable=2,021) with 5% significant. In other words, if both of those techniques compared, connected model assisted picture media have positive effect on the study’s product in learning science rather than direct instruction model.